2011
DOI: 10.1177/1076029611419841
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activity Indices in Patients With Deep Vein Thrombosis

Abstract: In patients with DVT, the presence of DVT was closely associated with increased platelet activation. The MPV, MPM, and MPC may identify patients requiring aggressive antiplatelet treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
(26 reference statements)
1
24
1
2
Order By: Relevance
“…39 Platelet activation occurs in patients with DVT. [6][7][8] Although conflicting results have been reported, 40 the majority of studies to date have highlighted an increase in platelet size with aging, 13 providing a potential explanation for higher thrombotic risk in aged individuals. [3][4][5] As larger platelets contain more granules and express procoagulant surface proteins and adhesion molecules, they display greater prothrombotic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Platelet activation occurs in patients with DVT. [6][7][8] Although conflicting results have been reported, 40 the majority of studies to date have highlighted an increase in platelet size with aging, 13 providing a potential explanation for higher thrombotic risk in aged individuals. [3][4][5] As larger platelets contain more granules and express procoagulant surface proteins and adhesion molecules, they display greater prothrombotic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation is a link in the pathophysiology of diseases prone to thrombosis and is viewed as a therapeutic target in thromboembolism. [6][7][8][9] Platelet size, measured as mean platelet volume (MPV), is considered a marker of its function and positively associated with indicators of platelet activity, including aggregation and production of thrombogenic factors, such as thromboxane A2, von Willebrand factor (VWF), platelet factor 4 (PF4), b-thromboglobulin, and P-selectin. [10][11][12] A number of population studies have shown that MPV and platelet activation increase with age, 13 implying an essential role of these factors in aging-related VTE.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between increased number of platelets and venous thrombosis was demonstrated by various studies 18,19 . Additionally, it was accepted that the PLR value obtained by dividing the number of platelets by the number of lymphocytes is an indicator of both inflammatory and thrombotic events [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…A study found that increased MPV values are an indicator in development of venous thromboses such as deep venous thrombosis and pulmonary embolism [16][17][18] . In a study by Kamisli et al, it was found that MPV and PDW values in acute period CVST patients were higher than those of controls, and the same values were also higher in patients with parenchymal lesions than those without 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, doppler US is the prefferred method because it is noninvasive, safe, and inexpensive. [4] Recent advances in automated blood cell analyzers have made it possible to obtain new information about platelets through the measurement of platelet indices, including mean platelet volume (MPV). MPV is an indicator of platelet activation, which has an important role in the pathophysiology of thrombosis.…”
Section: Introductionmentioning
confidence: 99%